GEOMETRI DAN FRAGMENTASI BATUAN HASIL PELEDAKAN MENGGUNAKAN METODE KUZ-RAM - Wulandari, Septi Wulandari; Muhammad Fadil Bellico; Dedy Yuli Ariadi (Retii, 2024)
Blasting is one of stage from mining activities aimed at destroying rock to facilitate the process of stripping overburden. One measure of the success of a blasting is the level of uniformity of the rock resulting from the explosion or fragmentation. The target for rock fragmentation resulting from blasting at PT. X, the target for rocks measuring more than 50 cm is less than 15%. Changes in blasting geometry were carried out by trial to a load size of 5.5 meters, a spacing of 5.5 meters, a depth of 5 meters, and a square zig zag drilling pattern resulting in an estimated size of rock fragmentation over 50 cm of 10.78% based on the Kuz-Ram method. Based on these simulations and estimates applied to blasting carried out over a period of 1 month, the results obtained were fragmentation with a material size of more than 50 cm of 9.92%. These results meet the company's targets and are in line with Kuz-Ram's estimates with an estimation accuracy of 92.02%.